Photoreactive-proton-generating hyaluronidase/albumin nanoparticles-loaded PEG-hydrogel enhances antitumor efficacy and disruption of the hyaluronic acid extracellular matrix in AsPC-1 tumors - Woo Tak Lee (Elsevier, 2021)
Depletion of tumor extracellular matrix (ECM) is viewed as a promising approach to enhance the antitumor efficacy of chemotherapeutic-loaded nanoparticles. Hyaluronidase (HAase) destroys hyaluronic acid-based tumor ECM, but it is active solely at acidic pHs of around 5.0 and is much less active at physiological pH. Herein, we report the development of our novel UV-light-reactive proton-generating and hyaluronidase-loaded albumin nanoparticles (o-NBA/HAase-HSA-NPs). The method to prepare the nanoparticles was based on pH-jump chemistry using o-nitrobenzaldehyde (o-NBA) in an attempt to address the clinical limitation of HAase. When in suspension/PEG-hydrogel and irradiated with UV light, the prepared o-NBA/HAase-HSA-NPs clearly reduced the pH of the surrounding medium to as low as 5.0 by producing protons and were better able to break down HA-based tumor cell spheroids (AsPC-1) and HA-hydrogel/microgels, presumably due to the enhanced HA activity at a more optimal pH. Moreover, when formulated as an intratumor-injectable PEG hydrogel, the o-NBA/HAase-HSA-NPs displayed significantly enhanced tumor suppression when combined with intravenous paclitaxel-loaded HSA-NPs (PTX-HSA-NPs) in AsPC-1 tumor-bearing mice: The tumor volume in mice administered UV-activated o-NBA/HAase-HSA-NPs and PTX-HSA-NPs was 198.2 ​± ​30.0 ​mm3, whereas those administered PBS or non-UV-activated o-NBA/HAase-HSA-NPs and PTX-HSA-NPs had tumor volumes of 1230.2 ​± ​256.2 and 295.4 ​± ​17.1 ​mm3, respectively. These results clearly demonstrated that when administered with paclitaxel NPs, our photoreactive o-NBA/HAase-HSA-NPs were able to reduce pH and degrade HA-based ECM, and thereby significantly suppress tumor growth. Consequently, we propose our o-NBA/HAase-HSA-NPs may be a prototype for development of future nanoparticle-based HA-ECM-depleting tumor-ablating agents.